Orthogonal plating method versus parallel plating method in the treatment of distal humerus fracture: A systematic review and meta-analysis. (September 2019) - Yu, Xianbin; Xie, Linzhen; Wang, Jinwu; Chen, Chunhui; Zhang, Chuanxu; Zheng, Wenhao
Abstract: Purpose: This systematic review and meta-analysis was performed to investigate the outcomes of orthogonal plating method and parallel plating method in the treatment of distal humerus fracture from the current literatures. Methods: The electronic literature database of Pubmed, Embase, and Cochrane library were searched in November 2018. The data operation time, union time, Mayo Elbow Performance Score (MEPS), range of motion (ROM) of elbow, arc of elbow flexion, arc of elbow extension, rate of excellent and good results and complications (including heterotopic ossification, transient ulnar nerve neuropathy and ankylosis) were extracted. Stata 14.0 software was used for our meta-analysis. Results: A total of 8 studies including 6 RCTs and 2 cohort studies met our inclusion criteria. This meta-analysis showed that there was no significant difference between the two groups regarding operation time, MEPS, ROM of elbow, arc of elbow flexion, arc of elbow extension and rate of excellent and good results at final follow-up (P = 0.50, P = 0.39, P = 0.87, P = 0.18, P = 0.58 and P = 0.59 respectively). However, the present meta-analysis demostrated that parallel plating method had significantly shorter union time than orthogonal plating method (P = 0.018). As for the complications (heterotopic ossification, transient ulnar nerve neuropathy and ankylosis), there was no significant difference between the two groups (P = 0.89, P = 0.08 and P = 0.29 respectively). Conclusion: Our meta-analysis suggested that both orthogonal plating and parallel plating method could achieve satisfactory outcomes with the similarly low complications in the treatment of distal humerus fracture. More RCTs are required for further research. Highlights: Parallel plating method had significantly shorter union time than orthogonal plating method. No significant differences were found regarding the functional outcomes between the groups. Both groups achieved satisfactory outcomes with similarly low complications in the treatment of distal humerus fracture.